THE EFFECT OF CAPITAL STRUCTURE ON PROFITABILITY WITH OWNERSHIP STRUCTURE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN THE 2020-2024 PERIOD - Aisyah, Sitti; Ramli, Anwar; Anwar, Anwar (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the effect of capital structure on profitability with ownership structure as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. Capital structure variables are measured using the Debt to Equity Ratio (DER), Return on Assets (ROA), and ownership structure consists of institutional ownership and managerial ownership. This study uses a quantitative approach with path analysis techniques and moderation regression tests with the help of SPSS 26 software. The sample selected using a purposive sampling technique, as many as 7 companies that meet the criteria from a total of 83 food and beverage manufacturing companies listed on the IDX. The data used is secondary data in the form of five years of financial reports. The results of the study indicate that capital structure does not have a significant effect on profitability. Institutional ownership weakens the relationship between capital structure and profitability, while managerial ownership strengthens the relationship between capital structure and profitability. It is concluded that ownership structure has an important role in increasing the effectiveness of the use of capital structure to increase profitability.Keywords: Capital Structure, Profitability, Institutional Ownership, Managerial Ownership